THE RESEARCH ON THE CARBAPENEMASE ENZYME PRODUCTION IN KLEBSIELLA PNEUMONIAE AT CAN THO GENERAL HOSPITAL - Huynh, Tu Tran; Nguyen, Thi Hai Yen; Nguyen, Thi Ngoc Han; Le, Thuy An (Cantho Journal of Medicine and Pharmacy, 2025)
Background: Carbapenem resistance in Klebsiella pneumoniae was recognized as a serious issue, increasing challenges in treating severe infections. Understanding antibiotic resistance patterns was deemed essential for developing effective prevention and treatment control measures to reduce the spread of resistant bacteria. Objectives:(1) To determine the carbapenemase enzyme production rate of Klebsiella pneumoniae isolated from clinical specimens of infected patients. (2) To determine the carbapenem resistance rate in Klebsiella pneumoniae. Materials and method: A cross-sectional descriptive study with a sample size of 73 specimens was conducted on clinical samples from patients infected with Klebsiella pneumoniae at Can Tho City General Hospital. Results: The carbapenemase enzyme production rate in carbapenem-resistant strains was 91.9%. The resistance rates to ertapenem, imipenem, and meropenem were notably high in the carbapenemase-producing bacterial strains, reaching 91.7%, 94.3%, and 97.1%, respectively. All bacteria resistant to two classes of antibiotics simultaneously produced carbapenemase, with a rate of up to 97.1%, and for all three antibiotics, the rate was 97%. The resistance rate to ertapenem was 49.3%, while resistance to imipenem and meropenem was 47.9%. The rate of dual resistance to two types of carbapenems was 46.6%, and the resistance rate to all three carbapenems was 45.2%. Conclusion: The carbapenemase enzyme production rate reached 91.9%. Particularly, the bacteria producing carbapenemase exhibited very high resistance to carbapenem antibiotics, reflecting that the primary resistance mechanism is the production of carbapenemase. The study demonstrates a high resistance rate to carbapenem antibiotics (ertapenem, imipenem, and meropenem) in Klebsiella pneumoniae.